Pancreatic ductal adenocarcinoma and acinar cells: a matter of differentiation and development?. Issue 3 (5th July 2011) - Rooman, Ilse; Real, Francisco X
Abstract : Pancreatic ductal adenocarcinoma (PDAC) has long been considered to arise from pancreatic ducts on the basis of its morphology, the occurrence of dysplasia in putative preneoplastic ductal lesions, and the absence of acinar dysplasia in the pancreas of patients with PDAC. However, evidence gathered through both in vitro studies and—more importantly—genetic mouse models of PDAC shows that ductal-type tumours can arise from acinar cells. These findings raise new important questions related to PDAC pathophysiology and call for in-depth studies of acinar cell differentiation in order to better understand PDAC biology. The authors review these issues and discuss how the novel findings should impact on future work aiming at early diagnosis and improved outcome of patients with PDAC.